The Impact of Manаgement on the Effectiveness in Socioeducational Institutions - Kriviradeva, Bozhidara; Stoynova, Atanasia (Student Niepełnosprawny. Szkice i Rozprawy, 2021)
This article presents the results of an empirical study, whose main purpose is to establish a managment style that is best for socio-educational organizations according to their specifity. The study was conducted in a government and three nongovernmental organizations. They were selected randomly. Two institutions work with smaller, the other two – with greater capacity. In the first part of the article we present the functioning of the institutions and the second part results from the empirical study.